Zonation Systems on New Student Admission Policies For Equality of Education in Indonesia - Sonia Rahma Feberliantika; Hasan Hariri; Showiyah Showiyah; Riswanti Rini (Edumaspul: Jurnal Pendidikan, 2021)
This research aims to show the problems that occur regarding the application of the new student admission system through the zoning system, the real impact and the implications of various constraints and problems from the application of the zoning system in acceptance of new students. This research is a literature research with data resources using previously study and information from trusted mass media. The results of the study explain that there are several problems that need to be resolved so that the application of the zoning system in the new student admissions policy can be carried out optimally. The problem is reducing the capacity of the achievement pathway, the condition of school accreditation is not evenly distributed, and many schools have inadequate classroom conditions. The impact of the implementation of the zoning system is that it makes it easier for students to attend school, equalizes the quality of schools, and creates perceptions of the limitations of school choices for students.